Analisis Dampak Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi (Studi Kab/Kota Di Jawa Timur) - Ferdian Andi Wijaya (Jurnal Simki Economic, 2019)
Government spending is part of fiscal policy, which is a government action to regulate the course of the economy by determining the amount of government revenues and expenditures each year, which is reflected in the State Budget (APBN) for national and Regional Revenue and Expenditure Budgets (APBD) for regions. or regional. The purpose of this study was to determine the effect of government spending on health, education, and infrastructure functions on economic growth partially or simultaneously. This study uses a quantitative approach. The technique used is associative. The sample used in this study used non-probability sampling and the sample used was 31 using a purposive sampling technique and analyzed using multiple linear regression analysis with SPSS software for windows version 23. The conclusions of this study are: (1) Government Expenditure on Health Function has no significant effect on economic growth. (2) Government Expenditure on Education Function has a significant effect on economic growth. (3) Government Expenditures on the Infrastructure Function have no significant effect on economic growth. (4) Government Expenditures on Health, Education, and Infrastructure Functions do not have a significant simultaneous (together) effect on economic growth.